Influence of elevated temperatures on the mechanical behavior of one-part coal ash geopolymer concrete with sodium metasilicate pentahydrate and sodium metasilicate anhydrous as alkaline activators - Samadi M.; Wong L.S.; Murali G.; Lim N.H.A.S.; Ayeni I.S. (Elsevier Ltd, 2025)
Geopolymers can be synthesized through either a one-part or two-part combination methodology. The aluminosilicate precursor is blended with an alkaline activator solution in the two-part mixture. Conversely, the one-part mixture technique incorporates water directly into the dry composite comprising the aluminosilicate precursor and solid activator. Using one-part geopolymer concrete (OPGC) stands out as a beacon of sustainability, presenting a compelling alternative to conventional cement concrete in construction projects. A noticeable gap exists in the extant literature on investigations on the response of OPGC when subjected to elevated temperatures. The study aims to evaluate the effect of elevated temperatures on the mechanical behavior of OPGC. Sodium metasilicate pentahydrate (SMP) and sodium metasilicate anhydrous (SMA) are the two types of one-part alkaline activators used to make OPGC. Fly ash was applied as a precursor, and bottom ash was varied from 25 % to 100 % as a substitute for sand in the mix designs of the OPGC specimens. The concrete specimens were characterized by their workability, compressive strength, microstructures, mineralogical properties, and thermal stability. The results revealed that OPGC specimens with SMP and SMA activators containing bottom ash, exposed to 100 C, exhibited increased compressive strength by 7.31 % and 39.09 %, respectively, compared to those exposed to 30 C. This trend persisted, with the highest enhancements observed at 200 C, reaching 37.62 % and 72.39 % for SMP and SMA, respectively. However, compressive strength declined at higher temperatures, with the most significant drop occurring at 800 C. X-ray Diffraction results and microstructural analysis confirmed that the optimized geopolymer concrete is characterized by a binding product in Sodium Aluminosilicate Hydrate (N-A-S-H) gels, forming a robust three-dimensional geopolymer network. This behaviour implies a high level of toughness for the optimized geopolymer concrete. The study underscored the importance of comprehending the bonding mechanism of geopolymer concrete activated with SMP and SMA against high temperatures, as it clarifies the scientific underpinnings of its thermal resilience and resistance to deterioration, thus guiding the advancement of durable and eco-friendly construction materials. ? 2024 Elsevier Ltd